INCORPORATION of NEEM LEAVES INTO SOIL TO CONTROL BACTERIAL WILT of TOMATO - Pontes, N. de C.; Kronka, Adriana Zanin [UNESP]; Moraes, M. F. H.; Nascimento, A. S.; Fujinawa, M. F. [UNESP] (Edizioni Ets, 2011)
The objective of this study was to evaluate the effect of incorporation of neem (Azadirachta indica) leaves into the soil for controlling bacterial wilt of tomato caused by Ralstonia solanacearum. The experiment was conducted in a greenhouse of the State University of Maranhao (Brazil). Dry and fresh neem leaves were incorporated in the soil in different amounts (0, 20, 40, 60, 80 and 100 g) and kept in it for different periods of time (0, 15, 30, 45 and 60 days). After each of these periods, seedlings inoculated with R. solanacearum were transplanted in the amended soil. Results showed positive effects in the disease control by incorporating neem leaves, with a reduction of wilting symptoms up to 100% with dry leaves and 78% with fresh leaves.
Keywords: Azadirachta indica; Ralstonia solanacearum; tomato; bacterial wilt; control